A New BBBC based LEACH Algorithm for Energy Efficient Routing in WSN (International Journal of Engineering and Computer Science, 2014)
The competing objectives of wireless sensor network for optimizing the scarce battery utilization with sending large amount of data to base station, constantly suggest for identifying energy efficient routing algorithm. To achieve this objective, in this paper a Big Bang Big Crunch (BBBC) based metaheuristic algorithm is proposed for the selection of Cluster Head in such a way so that its energy is used uniformly with delayed disintegration of network. For this purpose, the LEACH algorithm random clustering approach has been replaced by BBBC clustering. To evaluate the performance of our proposed BBBC based LEACH protocol we have compared it with random LEACH, Max Energy LEACH and k-means LEACH. Results showed improvement in energy conservation.